Spatial Commuting Patterns of German Regional Labour Markets: A Sustainability Perspective - Federico Tedeschi; Aura Reggiani; Peter Nijkamp (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2012)
This paper aims to investigate the relationship between commuting and spatial labour market developments in the framework of sustainability issues. To do so, we propose, first, an exploratory investigation of the effects of inbound commuter flows on employment in regional labour markets in Germany. Next, we address sustainability issues as a common umbrella for the relationship 'economy-transportation'. In this context, we show that the German production system is faced with negative environmental externalities, which are clearly associated with a specific transport mode, viz. the private car. Negative environmental externalities as a result of modal choices in Germany are confirmed by data from EU-15 countries. Public transport, in particular the train, appears to be more environmentally-benign. Our results bring to light that, on average, commuter flows have a positive and robust effect on employment in the receiving German labour market districts, while, for commuting flows, public transport, especially the train, is a more environmentally-benign mode of transport, compared with the car, in reducing greenhouse gas emissions and energy consumption. In the light of possible policy strategies, the paper argues that sustainability may lead to positive economic effects; in particular, the improvement of the public transport system, which can provide more opportunities for sustainable commuting patterns, may lead to favourable employment perspectives for the local or regional labour force.
Keywords: R41; R23; J61; 330